Research on the optimization of mechanical properties of triply periodic minimal surfaces in composite materials prepared with the assistance of acoustic fields - Shuai Guo; Xianliang Sheng; Anfu Guo; Wenlu Yang; Xiaolin Zhao; Shang Sui; Jiaqiang Li; Yufan Zhao; Meng Wang; Xin Lin (Journal of Materials Research and Technology)
Lattice structures have garnered significant attention due to their superior mechanical properties. However, while maintaining the lightweight advantages of lattice structures, further enhancing their strength is of paramount research significance. This paper proposes an optimized Gyroid Sin Square (GSS) gradient structure and fabricates composite materials and epoxy interpenetrating phase composites (IPCs) lattice structures using Laser Powder Bed Fusion (LPBF) combined with Acoustic Fields (AF). The mechanical characteristics were examined through uniaxial compression experiments. The findings suggest that the composite lattice shows remarkably greater specific energy absorption (SEA) in contrast to the initial lattice. With the introduction of AF, the z-axis gradient 5 wt% tungsten carbide (WC) composite GSS structure exhibited a 76.78% improvement in SEA compared to the uniform original structure. The IPCs demonstrated the highest plateau stress, which can be attributed to the physical interlocking between the epoxy resin and the substrate, effectively enhancing deformation resistance. However, due to the earlier densification of IPCs during loading, SEA is somewhat reduced compared to the composite structures. The addition of WC led to grain refinement and weakened the texture. Meanwhile, the acoustic streaming and cavitation effects generated by the AF reduced residual stress, ultimately improving the overall mechanical properties of the lattice structures.